Two-Dimensional Locomotion in a Soft Foam Robot Using Weight Redistribution - Majkut, Martin. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Robert White.; Committee: Chris Rogers, Matthew Woodward, and Barry Trimmer.; Keywords: Mechanical engineering, Robotics, and Materials Science.